Holistic Acupressure Training for Posyandu Cadres to Reduce Emesis in Pregnant Women - Altahira, Sutrisna; Hamzah, Hasty; Mutia, Wa Ode Nurul; Dewi, Nutrika Rahma; Amaliyah, Suci; Yanarianto, Aprila Setiani; Pratiwi, Ayu Nugrawati (Jurnal Abmas Negeri (JAGRI), 2025)
SEHAT (Holistic Acupressure Touch to Overcome Emesis Gravidarum) training for Posyandu cadres in supporting the health of pregnant women was held in Kondongia village, Lohia sub-district, Muna district on October 15–17, 2025. This activity aims to improve the skills of Posyandu cadres in performing acupressure as a non-pharmacological complementary effort to overcome emesis gravidarum. The implementation method includes socialization, theoretical and practical training, and direct assistance in the field. The results of the activity showed an increase in cadre skills. Before the training, 85,71% of cadres were in the category of unable or unskilled in performing acupressure techniques. After the training, cadre skills increased with 33,33% being able to perform acupressure with little guidance and 66,66% being able to do it independently and correctly. A positive impact was also seen in the condition of pregnant women who were the targets of assistance, where there was a significant decrease in the frequency of emesis gravidarum. Before acupressure, 49,33% of pregnant women experienced mild and 20% severe emesis gravidarum, while after the intervention, only 14,66% experienced mild, 4% severe, and 68% did not experience emesis gravidarum. These results indicate that acupressure is effective as a simple complementary therapy that can be taught to Posyandu cadres to improve the comfort of pregnant women and support holistic maternal health.